The Effect Of The Edgware Model On Mindfulness And Learning The Skills Of Passing And Dribbling In Futsal For Students - Hamuwd, Dawood Sabeh; Mohammad Kareem, Dr. Muhanad (Adolescência e Saúde, 2026)
The importance of this research lies in its being a serious scientific attempt by the researcher, through his experience in the (preparatory) stage, to benefit from the Egga model and know the extent of its impact on mindfulness and learning the passing and dribbling skills in futsal for students. As for the research problem: Through the researcher’s observation of the reality of skills learning among preparatory students, he noticed the existence of difficulties in learning football skills, in addition to weaknesses in psychological aspects such as self-confidence and motivation, which can be addressed by the Egga model. Therefore, the researcher saw the impact of this model on mindfulness and learning the passing and dribbling skills in futsal for students As for the second chapter, the researcher addressed the theoretical studies and previous studies. As for the third chapter: the researcher used the experimental method because it was suitable for the nature of the research problem, using the method of two equivalent groups (control and experimental) with a pre-test and post-test. The research population was determined, which is represented by the students of the preparatory stage (morning study) in Dhi Qar Preparatory School for Mathematical Sciences / for the academic year (2025/2026), and their number is 120 students. The researcher conducted his experiment on a sample consisting of 20 students who were divided into two groups, experimental and control, in a random way and by drawing lots. Section (A) was chosen as the control group, which implements the method followed by the subject teacher in learning the skills of passing and dribbling with futsal for students, and Section (B) was chosen as the experimental group, which implements the Edja model in learning the skills of passing and dribbling with futsal for students Chapter Four presented the research findings and their application, which were discussed. A clear improvement in the students' mental alertness and futsal skills was observed. Chapter Five presented the researcher's conclusions, demonstrating the development of the experimental group, which worked according to the IDEA model, compared to the control group, which worked according to the teacher's method. The researcher recommended adopting the educational units developed according to the IDEA model and applying them to other samples and skills